Studi Pengaruh Traffic Light terhadap Kinerja Protokol Routing GPSR pada Vanet - Damianus Dewa Pratama; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Vehicular Ad-Hoc Network (VANET) is a technology developed to provide communication services among vehicles. VANET aimed at improving road safety, necessary warning systems and so on. Before being able to communicate a very important process that must be done is the routing process. Routing process is a process to determine the path that will be passed by the information to be sent properly, efficiently, and precisely. The method to run this routing process is routing protocol. Based on several problems encountered in the urban environment, one of which is the clustering of vehicles caused by traffic light,a study is needed that examines the impact of movement flows and grouping of vehicles influenced by the presence of traffic light on the performance of routing protocol. Then a solution is needed, namely the implementation of a routing protocol that uses vehicle geographic information for the routing process, namely Greedy Perimeter Stateless Routing (GPSR) routing protocol. By using end-to-end delay, Packet Delivery Ratio, Overhead Routing, Normalized Routing Load and Convergence Time as test parameters. Based on the results from test parameters, scenario without traffic light has better results even though in Convergence time is still better if there is traffic light.